Critical Gerontology for Social Workers (Book collections on Project MUSE., 2022)
This original collection explores how critical gerontology can make sense of old age inequalities to inform social work research, policy and practice. Engaging with key debates on age-related human rights, the conceptual focus addresses the current challenges and opportunities facing those who work with older people.